2023
DOI: 10.1021/acs.jpclett.3c02050
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Formation in a 9,10-Bis(phenylethynyl)anthracene Dimer and Trimer Occurs by Charge Recombination Rather than Singlet Fission

Rasmus Ringström,
Zachary W. Schroeder,
Letizia Mencaroni
et al.

Abstract: We present an experimental study investigating the solvent-dependent dynamics of a 9,10-bis(phenylethynyl)anthracene monomer, dimer, and trimer. Using transient absorption spectroscopy, we have discovered that triplet excited state formation in the dimer and trimer molecules in polar solvents is a consequence of charge recombination subsequent to symmetry-breaking charge separation rather than singlet fission. Total internal reflection emission measurements of the monomer demonstrate that excimer formation ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Furthermore, we did not observe any spectral features corresponding to the BPEA radical anion or cation in the performed pump−probe experiments. 43 This indicates a concerted double electron transfer Dexter-type process in which the donor and acceptor overall remain electrically neutral and that does not occur via sequential electron transfer steps, thereby not requiring large solvent reorganization and explaining the solvent-independent TET kinetics. 44,45 The TET efficiencies (η TET ) of the three BPEA derivatives were calculated using the following formula 14,46 1 TET YbNP@NdNP@BPEA GdNP@BPEA = Where τ YbNP@NdNP@BPEA and τ GdNP@BPEA are the decay times of the T n ← T 1 PIA of BPEA when coordinated to YbNP@ NdNPs, i.e., in the presence of TET, and GdNPs, i.e., in the absence of TET, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Furthermore, we did not observe any spectral features corresponding to the BPEA radical anion or cation in the performed pump−probe experiments. 43 This indicates a concerted double electron transfer Dexter-type process in which the donor and acceptor overall remain electrically neutral and that does not occur via sequential electron transfer steps, thereby not requiring large solvent reorganization and explaining the solvent-independent TET kinetics. 44,45 The TET efficiencies (η TET ) of the three BPEA derivatives were calculated using the following formula 14,46 1 TET YbNP@NdNP@BPEA GdNP@BPEA = Where τ YbNP@NdNP@BPEA and τ GdNP@BPEA are the decay times of the T n ← T 1 PIA of BPEA when coordinated to YbNP@ NdNPs, i.e., in the presence of TET, and GdNPs, i.e., in the absence of TET, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…[69] It has been reported before that, despite of the significant endothermicity between S 1 and triplet pair (E 2XT1 -E S1 > 0.4 eV), [70] an An chromophore and its derivatives can undergo intermolecular SF in crystals or thin films, [71][72][73][74][75][76] whereas intramolecular SF channel is not activated in the dimer in the solution phase. [77][78][79][80] This is presumably due to the efficient orbital interaction between adjacent chromophores in the solid phase, which could activate the CT-mediated mechanism. [52,81,82] Recently, it also has been reported that in acene dimers, the presence of an allowed CT state in the steady-state absorption spectrum can be regarded as an important factor to expect whether molecules can undergo efficient intramolecular SF or not.…”
Section: Nanosecond Transient Absorption: Triplet Formation Dynamicsmentioning
confidence: 99%
“…As for the intermolecular mechanism, the optically excited singlet state on one molecule couples with a neighboring molecule in its ground state to form the biexciton state, which can subsequently separate into two independent triplets, localized on the two distinct molecules. This mechanism is generally operative when aggregate species are formed, either in the solid state or in concentrated solutions. On the other hand, intramolecular SF occurs with the biexciton and the two independent triplets located on the same molecule and, thus, it has been invoked in the literature for large size multichromophoric molecular systems, such as dimers, oligomers, and polymers. The biggest advantage of covalent systems is that the electronic coupling between chromophores can be tailored synthetically, thus giving much finer control over the parameters driving SF than is possible via film engineering or aggregation. Our research group has recently reported evidence of endothermic SF in a new class of thermally and photochemically stable fluorene derivatives, showing high-energy triplet excitons (1.8–2.0 eV), particularly appealing in view of possible photovoltaic applications .…”
Section: Introductionmentioning
confidence: 99%